Generation of a symmetrical trispecific NK cell engager based on a two-in-one antibody - Harwardt, Julia; Carrara, Stefania C.; Bogen, Jan P.; Schoenfeld, Katrin; Grzeschik, Julius; Hock, Björn; Kolmar, Harald (Frontiers in Immunology, 2023)
To construct a trispecific IgG-like antibody at least three different binding moieties need to be combined, which results in a complex architecture and challenging production of these molecules. Here we report for the first time the construction of trispecific natural killer cell engagers based on a previously reported two-in-one antibody combined with a novel anti-CD16a common light chain module identified by yeast surface display (YSD) screening of chicken-derived immune libraries. The resulting antibodies simultaneously target epidermal growth factor receptor (EGFR), programmed death-ligand 1 (PD-L1) and CD16a with two Fab fragments, resulting in specific cellular binding properties on EGFR/PD-L1 double positive tumor cells and a potent ADCC effect. This study paves the way for further development of multispecific therapeutic antibodies derived from avian immunization with desired target combinations, valencies, molecular symmetries and architectures.